The formulation and microstructural, rheological, and textural characterization of salep-xanthan gum-based liposomal gels - Saroglu, Oznur; Karadag, Ayse; Tekin-Cakmak, Zeynep Hazal; Karasu, Salih (SPRINGER, 2023)
This study aimed to determine the morphological, Rheological, and textural characterization of xanthan gum-salep liposomal gels. The particle size of liposomes (94.21 +/- 0.57 nm) was increased in liposomal gels, and it was highest (116.83 +/- 1.97 nm) in the K1S3 formulation. The surface charge of liposomes was - 37.40 +/- 3.05 mV, and it was significantly decreased by the addition of polymers, changing between - 28.53 and - 30.63 mV. SEM analysis showed that the hydrogel and liposomal gels did not have any aggregation and had a bird net porous morphology and uniform distribution of liposomes. FTIR analysis revealed an interaction between xanthan gum-salep and lecithin. TEM analysis showed spherical structures of liposomes with no obvious aggregation and their size determined by TEM complied with the results taken by DLS analysis. The rheological properties of hydrogels and liposomal gels were characterized by steady shear, frequency, and temperature sweep test, and 3-ITT analysis. All hydrogels and liposomal gels samples showed non-Newtonian, solid-like, and recoverable characters, which increased with an increase in salep concentration in gel formulation. The textural properties of the both hydrogels and liposomal gels were significantly affected by salep-xanthan gum concentration in gels. The results of this study suggested that xanthan gum-salep liposomal gels with strong mechanical properties could be produced by increasing the salep ratio in gel formulation.
Keywords: Liposomal gels; Rheology; TEM; PROFILE ANALYSIS; CONTROLLED-RELEASE; DRUG-DELIVERY; HYDROGEL; ADHESIVE; BEHAVIOR; ANTIOXIDANT; LECITHIN; GELATIN; BOVINE; Polymer Science